LENS: a lyric meditation. Issue 2 (3rd April 2018) - Coles, Katharine
ABSTRACT: This lyric/scholarly meditation engages perception and vision in both the scientific and the personal senses of the words, with an eye in particular on how the lenses we use for seeing (both such instruments as microscopes, telescopes, and spectacles on the one hand and constructions like theories and hermeneutics on the other) not only enable us to perceive what is beyond us but also shape and sometimes distort what we perceive. The essay also considers how creative works, and in particular narrative and lyric writings, operate at once as instruments by which perceptions are communicated and as tools for forming and shaping our perceptions. Finally, 'Lens' addresses and enacts ways in which the construction of the literary work, like the construction of an instrument, shapes what we can use it to observe and consider.